1995
DOI: 10.1021/ja00146a038
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Conformation-Directing Effects of Secondary Hydrogen-Bonding Interactions in Flexible Tetrapeptide Analogs

Abstract: Hydrogen bonds are involved in many interand intramolecular recognition processes, but simply counting the hydrogen bonds in a complex or folding pattern does not necessarily provide insight on stability.1 In 1990, Jorgensen and Pranata pointed out that variations among the association constants for a series of triply hydrogen bonded complexes, including the guanine-cytosine base pair, could be rationalized in terms of "secondary interactions" among the hydrogen-bonding groups.2 These secondary interactions in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 0 publications
5
26
0
Order By: Relevance
“…255,256 This result accords with DauberOsguthorpe et al's modeling study, which predicted that a six-membered hydrogen bonded ring arrangement of Ac-gAla-Ac is less stable than the extended conformation; but it contrasts with the predictions of Alemá n and Pérez and Stern et al that such an arrangement is the minimum energy conformation for Ac-gGly-Ac (section VI.C.3, above).…”
Section: The New Residuessupporting
confidence: 82%
See 1 more Smart Citation
“…255,256 This result accords with DauberOsguthorpe et al's modeling study, which predicted that a six-membered hydrogen bonded ring arrangement of Ac-gAla-Ac is less stable than the extended conformation; but it contrasts with the predictions of Alemá n and Pérez and Stern et al that such an arrangement is the minimum energy conformation for Ac-gGly-Ac (section VI.C.3, above).…”
Section: The New Residuessupporting
confidence: 82%
“…However, Gardner and Gellman found that their IR spectroscopic data, while consistent with the two state equilibrium depicted in Figure 13, yielded very similar equilibrium constants for the parent and PMRI depsipeptides (K ≈ 0.6, in dichloromethane). 255,256 Therefore secondary interactions do not increase the -folding propensity of 115 over that of its parent, in this case, probably because intramolecular dipoledipole repulsions result in nonplanarity of the amide groups, 255,256 a situation that cannot arise within the rigid heterocyclic systems found in nucleotide bases.…”
Section: The New Residuesmentioning
confidence: 92%
“…The most striking feature of this study indicates that the net contribution of enthalpic as well as entropie parameters in overall AG at ambient temperature is roughly comparable with those reported for other hydrogen bonded secondary structural elements mimicking various reverse turns, e.g. ß-and y-turn conformations [14,[18][19][20]23,24]. It is pertinent to note that the enthalpy-entropy internal compensation effects are the consequences of the unique complex phenomenon of flexible and/or conformationally restricted geometries of the structures and the solvent properties interacting with them.…”
Section: Resultssupporting
confidence: 81%
“…SIH was eagerly seized by the supramolecular community (e.g. [5][6][7][8][9][10]), which was then (and perhaps still is) in need for back-of-the-envelope guidance on complex stability beyond that given by hydrogen bonding. However, SIH is also known to fail or require further modification [5,6,[11][12][13].…”
Section: Introductionmentioning
confidence: 99%